2018
DOI: 10.1680/jgere.17.00015
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear elastic model incorporating temperature effects

Abstract: The objective of this paper is to present a non-linear elastic model, considering temperature effects, that engineers can readily use to predict the mechanical behaviours of soils in geotechnical applications. Instead of using hyperbolic and exponential models, a non-linear equation is first formatted to describe the tangent moduli for saturated clays by introducing only one additional parameter (i.e. p ). By extending the non-linear equation, a new simplified nonlinear elastic model is obtained that is capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Amiri et al (2018) used multiple linear regression to estimate unsaturated shear strength parameters using several indices of the physical properties of soil as function inputs. Liu et al (2018) reported on the relationships between the mechanical properties of clays and temperature. Motaghedi and Eslami (2014), Mcgann et al (2015), Cao and Wang (2013), Lim et al (2020), and Schneider et al (2008) empirically linked data from CPT on sleeve friction, cone tip resistance, and porewater pressure data to soil properties including cohesion, friction angle, soil classification, overconsolidation ratio, and shear wave velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Amiri et al (2018) used multiple linear regression to estimate unsaturated shear strength parameters using several indices of the physical properties of soil as function inputs. Liu et al (2018) reported on the relationships between the mechanical properties of clays and temperature. Motaghedi and Eslami (2014), Mcgann et al (2015), Cao and Wang (2013), Lim et al (2020), and Schneider et al (2008) empirically linked data from CPT on sleeve friction, cone tip resistance, and porewater pressure data to soil properties including cohesion, friction angle, soil classification, overconsolidation ratio, and shear wave velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Lo et al (2016) presented a one-dimensional consolidation theory in unsaturated soils under cyclic loading. Wang et al (2017), Liu et al (2018), Zou et al (2018), and Zhao et al (2020), respectively, obtained analytical solutions for the one-dimensional consolidation of clayey soils considering different load and boundary conditions. When considering time-dependent loading, Deng et al (2019) presented closedform solutions for one-dimensional consolidation in saturated soils, Moradi et al (2019) analyzed the one-dimensional consolidation of a multilayered unsaturated soil under partially permeable boundary conditions, and Zhou et al (2020) obtained an analytical solution for a classical one-dimensional thaw consolidation model.…”
Section: Introductionmentioning
confidence: 99%
“…Based on environmental tests, the sediments were assessed as uncontaminated and could be reused directly without a decontamination treatment process. Liu et al (2018a) developed a non-linear elastic model, considering temperature effects that engineers can readily use to predict the mechanical behaviours of soils in geotechnical applications. In this model, all of the eight parameters have clear physical meanings and could be readily obtained by performing temperature-controlled triaxial tests.…”
mentioning
confidence: 99%